Assessment of primary and inflammation-driven genotoxicity of carbon black nanoparticles in vitro and in vivo. Issue 4 (21st April 2022) - Di Ianni, Emilio; Møller, Peter; Cholakova, Tanya; Wolff, Henrik; Jacobsen, Nicklas Raun; Vogel, Ulla
Abstract: Carbon black nanoparticles (CBNPs) have a large surface area/volume ratio and are known to generate oxidative stress and inflammation that may result in genotoxicity and cancer. Here, we evaluated the primary and inflammatory response-driven (i.e. secondary) genotoxicity of two CBNPs, Flammruss101 (FL101) and PrintexXE2B (XE2B) that differ in size and specific surface area (SSA), and cause different amounts of reactive oxygen species. Three doses (low, medium and high) of FL101 and XE2B were assessed in vitro in the lung epithelial (A549) and activated THP-1 (THP-1a) monocytic cells exposed in submerged conditions for 6 and 24 h, and in C57BL/6 mice at day 1, 28 and 90 following intratracheal instillation. In vitro, we assessed pro-inflammatory response as IL-8 and IL-1β gene expression, and in vivo, inflammation was determined as inflammatory cell infiltrates in bronchial lavage (BAL) fluid and as histological changes in lung tissue. DNA damage was quantified in vitro and in vivo as DNA strand breaks levels by the alkaline comet assay. Inflammatory responses in vitro and in vivo correlated with dosed CBNPs SSA. Both materials induced DNA damage in THP-1a (correlated with dosed mass), and only XE2B in A549 cells. Non-statistically significant increase in DNA damage in vivo was observed in BAL cells. In conclusion, this study shows dosed SSA predicted inflammation both in vivo and in vitro, whereas dosed mass predicted genotoxicity in vitro in THP-1a cells. The observed lack of correlation between CBNP surface area and genotoxicity provides little evidence of inflammation-driven genotoxicity in vivo and in vitro .